A CRITICAL REVIEW OF RASAOUSHADIES IN THE MANAGEMENT OF NETRA ROGAS (EYE DISEASES) - T Rathod, *Padmavathi; KV, Mamatha; Gopal, Dr; K, Sujathamma (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda chikitsa paddhati, Rasa oushadhis has been considered more useful and effective as they are more advantageous due to their unique benefits over the other preparations. Medicines described to manage different diseases in our classical texts contain different sources like plants, marine, animals, minerals and metals. All these are formulated in such a way that it suits well to our body. This clearly states that there were usage of herbomineral preparations in therapeutics which includes for Netrarogas also. These preparations are significant in many chronic and challenging eye disorders of this era which lacks curative rate and has high recurrences. To deal such challenging disorders of the Eye whether chronic or newly existing, essential to review and re-establish the importance of Rasa oushadhis which are explained by our Acharyas pertaining to Netra rogas, with regard to its route of administration and posology. For this Review work, information were compiled from different texts according to Rasadravyas mentioned as Chakshushya and to treat Netra rogas i.e., Maharasa, Uparasa, Sadharanrasa, Dhatu, Ratna, Sudha varga. Further the different Yogas of Netra Roga containing Rasadravyas as one of the ingredients is compiled as an attempt to establish Rasaushadhi - the need of the hour for Netra Rogas.